The Predictors of Career Success - Alzyoud, Adel Ali Yassin (International Review of Management and Marketing, 2017)
This study was carried out to examine the relationship between career commitment, career values perceived organizational support and career success. Using convenient sampling, data was gathered using 291 questionnaires. Correlation and regression analysis were performed to determine the significance of the independent variables, career values and perceived organizational support on career success. Analysis of the data revealed that career commitment, career values and perceived organizational support have significant but moderate relationship with career success. The findings show that variables, that is, career commitment, career values and perceived organizational support influence approximately 61 percent variance on career success. This means there other factors that could not be explained by this study that determine career success. Future research should look at other variables such as human capital, socio-demographic status and stable individual difference that might influence career success. Keywords: career commitment, career values, perceived organizational support, career success JEL Classifications: L2, L22, L25